Integrasi Nilai Islam dan Budaya Lokal dalam Tradisi Khitan Anak Laki-Laki di Desa Lamu - Olfin Anuke; Sutrisno Mohamad; Renol Hasan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the integration of Islamic values and local culture in the tradition of male circumcision in Lamu Village as a living socio-religious practice within the community. The background of this study is based on the existence of the circumcision tradition, which is understood not only as a religious obligation but also as a cultural expression that has undergone a process of social adaptation and reinterpretation. The study employs a descriptive qualitative approach through field research using participatory observation, in-depth interviews, and documentation of tradition practitioners, parents, as well as religious and traditional leaders. Data analysis was conducted thematically through data reduction, data presentation, and drawing conclusions with triangulation validation of sources. The research findings indicate that the circumcision tradition functions as a medium for the internalization of Islamic values, a means of religious education for children, and a mechanism for community social integration through symbols, rituals, and collective practices. The integration of religion and culture occurs dialogically through the selection of customary elements that align with Islamic norms. The novelty of this research lies in its empirical explanation of circumcision as a space for socio-religious transformation that demonstrates the harmonization of Islamic identity and local wisdom within the context of rural society.